2017
DOI: 10.1093/ntr/ntx085
|View full text |Cite
|
Sign up to set email alerts
|

A Proactive Smoking Cessation Intervention for Socioeconomically Disadvantaged Smokers: The Role of Smoking-Related Stigma

Abstract: Smoking denormalization has led to increased perceptions of smoking-related stigma among many smokers; however, little is known about how this stigma influences the cessation process. In the present study, smokers with lower levels of perceived smoking-related stigma lived in social environments that were more conducive to smoking and were less motivated to quit than higher stigma smokers. Despite these barriers, our proactive outreach cessation intervention was more effective for lower stigma smokers, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…In a recent intervention trial, low income smokers who reported higher levels of baseline stigma were less likely to engage in a smoking cessation intervention. 31 Stigma has been associated with misreporting of smoking status to health care providers, particularly in hospitalized smokers and those with chronic medical conditions. 30,32 These findings highlight the importance of gaining a greater understanding of the role of stigma as a barrier for smoking cessation including a focus on tailoring cessation interventions to optimize engagement and cessation outcomes.…”
Section: An Intrapersonal (Individual) Perspective To Addressing Lungmentioning
confidence: 99%
“…In a recent intervention trial, low income smokers who reported higher levels of baseline stigma were less likely to engage in a smoking cessation intervention. 31 Stigma has been associated with misreporting of smoking status to health care providers, particularly in hospitalized smokers and those with chronic medical conditions. 30,32 These findings highlight the importance of gaining a greater understanding of the role of stigma as a barrier for smoking cessation including a focus on tailoring cessation interventions to optimize engagement and cessation outcomes.…”
Section: An Intrapersonal (Individual) Perspective To Addressing Lungmentioning
confidence: 99%
“…43 On the other hand, higher-SES individuals who continue to smoke despite lower levels of nicotine dependence, high social and environmental pressures to quit, and many available quit resources may be resistant to additional outreach. Additionally, recent work by Hammett and colleagues 59 confirmed that low-SES smokers often experience lower levels of perceived smoking-related stigma, or the social unacceptability of smoking. Low-SES smokers with a lower level of perceived smoking-related stigma at baseline reported higher abstinence rates at 1-year in response to a proactive outreach intervention than those with higher baseline levels of smoking-related stigma.…”
Section: Discussionmentioning
confidence: 95%
“…Future trials of outreach to smokers, which are increasingly relying on mobile health technology, 61,62 interactive voice response, 57 and text messaging, 61,63À65 should evaluate how those technologies address the needs of smokers at all SES levels. 59…”
Section: Discussionmentioning
confidence: 99%
“…In relation to social norms, research in the general population has shown that social stigma, or the perception of being discriminated against, influences smoking and quitting behavior (Hammett et al, 2017;O'Connor, Rees, Rivard, Hatsukami, & Cummings, 2017;Stuber, Galea, & Link, 2008). Among smokers with mental illness, greater levels of self-stigma regarding smoking were associated with greater readiness to quit (Brown-Johnson et al, 2015), but we are not aware of research that has evaluated perceptions of smoking-related stigma among young adult smokers with SMI.…”
mentioning
confidence: 91%